Analisis Putusan Tindak Pidana Pemerkosaan Pada Anak Di Bawah Umur: (Studi Putusan Pengadilan Negeri Limboto Nomor: 115/PID.sus/2022/PN.LBO) - Syifah Aziza Ismail; Lisnawaty W. Badu; Julisa Aprilia Kaluku (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research aims to analyze the Decision of the Limboto District Court Number: 115/PID.sus/2022/PN.LBO concerning the Crime of Rape. This research is normative research with a statutory approach and a case approach, which is analyzed descriptively. The research results show that Decision Number 115/Pid.Sus/2022/Pn.Lbo is viewed from the aspect of certainty, namely, the decision does not reflect the principle of legal certainty. Considering that Article 81 (Paragraph 3) imposed in the indictment and verdict carries a penalty of 15 years in prison plus 1/3, the defendant should be subject to a sanction of 20 years in prison. Meanwhile, the prosecutor demanded 14 years, which the judge then reduced by giving a sanction of only 11 years in prison. Discussing the element of certainty is not just a moral demand, but factually it characterizes actual law and is based on the constitution, namely Article 1 Paragraph 3 of the 1945 Constitution of the Republic of Indonesia, where Indonesia is a rule of law state. Apart from that, the principle of legal certainty is said to have not been fulfilled, because the judge in giving his decision was not guided by Article 64 paragraph (1) of the Criminal Code. Furthermore, laws are essentially made and must not give rise to doubt, so as not to conflict with the objectives of the norm itself. Legal certainty refers to the consistent application of law where its implementation cannot be influenced by subjective circumstances.